2008
DOI: 10.1111/j.1600-0420.2007.01050.x
|View full text |Cite
|
Sign up to set email alerts
|

Complement factor H Y402H polymorphism and characteristics of exudative age‐related macular degeneration lesions

Abstract: . Purpose:  The Y402H polymorphism of the complement factor H (CFH) gene is associated with age‐related macular degeneration (AMD) in many populations. The reported genotype−phenotype correlations in the CFH Y402H polymorphism have not been pronounced and no studies on the effect of the polymorphism on the subgroups within wet AMD have been performed. In this study, we wanted to evaluate whether the CFH Y402H polymorphism has an effect on clinical variables in recent exudative AMD lesions. Methods:  The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 22 publications
2
12
0
2
Order By: Relevance
“…These results are consistent with previous reports in Asian populations [32]. In addition to the association between genotypes and disease pathogenesis [33-35], there have been many reports on CFH polymorphism as a predictor of treatment response in Caucasian populations, such as the response to zinc supplements [36], photodynamic therapy (PDT) [37-39], and intravitreal antivascular endothelial growth factor (VEGF) agents such as intravitreal bevacizumab [40] and ranibizumab treatment [41]. Anti-VEGF, which is now a standard treatment for exudative AMD, causes regression of neovascularization and has an anti-inflammatory effect.…”
supporting
confidence: 93%
“…These results are consistent with previous reports in Asian populations [32]. In addition to the association between genotypes and disease pathogenesis [33-35], there have been many reports on CFH polymorphism as a predictor of treatment response in Caucasian populations, such as the response to zinc supplements [36], photodynamic therapy (PDT) [37-39], and intravitreal antivascular endothelial growth factor (VEGF) agents such as intravitreal bevacizumab [40] and ranibizumab treatment [41]. Anti-VEGF, which is now a standard treatment for exudative AMD, causes regression of neovascularization and has an anti-inflammatory effect.…”
supporting
confidence: 93%
“…Seitsonen et al found no correlation between CNV size and CFH Y402H genotype in patients with wet AMD. However they did find a non-significant association in patients with the homozygous at-risk CC allele and incidence of minimally classic CNV (Seitsonen et al 2008a). Leveziel et al (2008) found individuals with wet AMD, with the homozygous Y402H genotype were more likely to have minimally classic CNV, although numbers were relatively small in each group.…”
Section: Cfh Polymorphisms and Amd Phenotype Correlationsmentioning
confidence: 95%
“…In Caucasian populations, variants in the complement factor H gene have been shown to be consistently associated with an increased risk for AMD. [66][67][68][69] Although these findings strongly indicate that the innate immune system is implicated in the mechanisms that lead to AMD, other factors have been discussed as well. Among others, a primary vascular component has been proposed as contributing to AMD pathophysiology.…”
Section: Degenerationmentioning
confidence: 92%